Calculation of GIC in the North Island of New Zealand Using MT Data and Thin‐Sheet Modeling. Issue 11 (21st November 2020) - Mukhtar, K.; Ingham, M.; Rodger, C. J.; Mac Manus, D. H.; Divett, T.; Heise, W.; Bertrand, E.; Dalzell, M.; Petersen, T.
Abstract: Geomagnetically induced currents (GICs) in the North Island New Zealand power transmission network during two large magnetic storms are calculated from both magnetotelluric (MT) data and a thin‐sheet conductance model of New Zealand previously used to study GIC in the South Island. We focus on the 2015 St. Patrick's Day magnetic storm and the storm of 20 November 2003. Lack of MT data in the northwestern part of the Island means that the transmission network in this region is represented by an equivalent circuit. Lack of GIC observations in the North Island means that results cannot be directly compared with measured GIC. However, our calculation of GIC shows that substations and individual transformers in the lower part of the Island with significant currents are generally the same as those where total harmonic distortion has been observed during periods of enhanced geomagnetic activity. MT data in the period range 2–30 min are used to predict GIC associated with the sudden storm commencement and rapid variations in the magnetic field. In contrast, the thin‐sheet modeling approach shows that GIC may be expected to occur in conjunction with longer‐period variations. Calculations for the 2003 storm suggest that at some locations GIC in excess of 10 A may persist for long periods of time and may produce significant harmonic distortion which could lead to localized transformer heating. It is concluded that despite its relatively low latitude the North Island power network is potentially at risk from significant GIC during extreme storms. Plain Language Summary: Variations in the Earth's magnetic field with time during so‐called "magnetic storms" can result in currents (geomagnetically induced currents—GICs) entering and leaving power transmission lines through the ground connections on transformers. Large GIC, or even smaller currents occurring repeatedly, can not only damage transformers but, in the worst‐case scenario, cause disruption to an entire transmission network. To attempt to assess the potential vulnerability of the transmission network in the North Island of New Zealand to such effects, we present model calculations of GIC resulting from two magnetic storms. The results show that despite the relatively low geomagnetic latitude of New Zealand's North Island, there are some substations and individual transformers where large GIC can be expected and may be problematic. Key Points: GIC in the North Island of New Zealand was modeled for the St. Patrick's Day 2015 storm and the storm of 20 November 2003 Calculations based on MT data and thin‐sheet modeling were compared Substations and individual transformers that may be at risk during significant space weather events were identified